Investigating the crowd-drawing effect, on passersby, of pseudo-crowds using multiple robots. (19th March 2023) - Amada, Joichiro; Okafuji, Yuki; Matsumura, Kohei; Baba, Jun; Nakanishi, Junya
Abstract : Due to their conversational skills, service robots are expected to replace posters or digital signage as a new advertising medium. These robots must achieve two goals to obtain maximum advertising opportunities in a public space: they must stop as many passersby as possible and make passersby stay as long as possible. In previous studies, to achieve these goals, the robots called out to each passerby one by one, which was inefficient as an advertising medium. Therefore, to obtain more advertising opportunities, this study proposes a method to simultaneously stop many passersby and make them stay, by creating a pseudo-crowd with multiple robots. The pseudo-crowd is a system in which multiple robots acting as an audience are placed around a robot providing information. We verified the effectiveness of the proposed method in a shopping mall. As a result, increasing the number of robots made more passersby stop, and the use of audience robots extended the time passersby spent in front of the robots. Our findings will contribute to the application of robots as a more useful advertising medium in public spaces. GRAPHICAL ABSTRACT: UF0001